A Non-linear Relationship Between Selective Attention and Associated ERP Markers Across the Lifespan - Reuter, Eva-Maria; Vieluf, Solveig; Koutsandreou, Flora; Hübner, Lena; Budde, Henning; Godde, Ben; Voelcker-Rehage, Claudia (Frontiers in Psychology, 2019)
The ability to selectively attend to task relevant information increases throughout childhood and decreases in older age. Here, we intended to investigate these opposing developmental trajectories, to assess whether gains and losses early and late in life are associated with similar or different electrophysiological changes, and to get a better understanding about the development in middle-adulthood. We (re-)analysed behavioural and electrophysiological data of 211 participants, who performed a coloured Flanker task while their EEG was recorded. Participants were subdivided into six groups depending on their age, ranging from 8-83 years. We analysed response speed and accuracy as well as the event replated potential (ERP) components P1 and N1, associated with visual processing and attention, N2 as marker of interference suppression and cognitive control, and P3 as a marker of cognitive updating and stimulus categorisation. Response speed and accuracy were low early and later in life, with peak performance in young adults. Similarly, ERP latencies of all components and P1 and N1 amplitudes followed a u-shape pattern with shortest latencies and smallest amplitudes occurring in middle-age. N2 amplitudes were larger in children, and for incongruent stimuli in adults middle-aged and older. P3 amplitudes showed a parietal-to-frontal shift with age. Further, group-wise regression analyses suggested that children’s performance depended on cognitive processing speed, while older adults’ performance depended on cognitive resources. Together these results imply that different mechanisms restrict performance early and late in life and suggest a non-linear relationship between electrophysiological markers and performance in the Flanker task across the lifespan